1971
DOI: 10.1063/1.1674732
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Mechanical Transition Probabilities for Atom–Atomic-Oscillator Collisions with Morse Potential Interaction

Abstract: Exact quantum-mechanical transition probabilities for the collision of an atom with an atomic oscillator for the case in which the interaction has the form of a Morse potential are obtained by numerical integration of the relevant close-coupled scattering equations. These transition probabilities are compared with approximate ones calculated from distorted-wave theory over a range of parameters which have been of interest in examining the collision of helium atoms with a tungsten surface. Some information is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1975
1975

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…1. Z is the separation of incident atom A from oscillator atom B measured from the minimum in the Morse potential, Zoo The potential is (1) in which E is the well depth and L is the usual parameter associated with the steepness of the potentiaL Heidrich, Wilson, and R app6 have shown that for a Morse potential between an atom and a harmonic oscillator the average energy transferred on collision, in which there is (2) in which tJ> = tan-ie (E/ Eo)1/2J, a and m are dimensionless parameters and …”
Section: Methodsmentioning
confidence: 99%
“…1. Z is the separation of incident atom A from oscillator atom B measured from the minimum in the Morse potential, Zoo The potential is (1) in which E is the well depth and L is the usual parameter associated with the steepness of the potentiaL Heidrich, Wilson, and R app6 have shown that for a Morse potential between an atom and a harmonic oscillator the average energy transferred on collision, in which there is (2) in which tJ> = tan-ie (E/ Eo)1/2J, a and m are dimensionless parameters and …”
Section: Methodsmentioning
confidence: 99%